TEACHING THE STRUCTURE AND OPERATING PRINCIPLES OF MRI DEVICES IN MEDICAL UNIVERSITIES THROUGH AN INNOVATIVE APPROACH - Sodikova Dilnavoz Kambaralievna (Modern American Journals, 2025)
Magnetic Resonance Imaging (MRI) represents one of the most advanced diagnostic tools in contemporary medicine, making it essential for medical universities to provide future physicians with comprehensive, technologically informed training. This article explores innovative pedagogical approaches for teaching the structure and operating principles of MRI devices, focusing on the integration of simulation technologies, virtual reality interfaces, interactive parameter adjustment modules, and interdisciplinary instruction. Traditional theoretical teaching often fails to convey the complexity of MRI physics, device components, and clinical application, whereas innovative, practice-oriented models significantly enhance comprehension and learner engagement. The article presents a unified discussion of MRI subsystems—including superconducting magnets, gradient coils, RF transmit–receive systems, cooling mechanisms, and computational processing units—and analyzes how innovative teaching strategies improve students’ understanding of image formation, safety protocols, contrast administration, and artifact recognition. Two comparative tables illustrate MRI components and differences between traditional and innovative educational approaches. The study concludes that modernizing MRI education through interactive and technology-driven methods fosters deeper conceptual insight, strengthens clinical readiness, and prepares medical students for rapid advancements in imaging sciences.
Keywords: MRI education; medical universities; innovative teaching; magnetic resonance imaging; simulation-based learning; MRI structure; superconducting magnet; gradient coils; RF systems; clinical imaging; virtual reality teaching; medical physics; diagnostic technology training.